Determinants of Community Willingness for COVID-19 Booster Vaccination at Pengasinan Health Center in Bekasi City - Putri, Syafira Berliana; Azteria, Veza; Febriyanty, Deasy; Nitami, Mayumi (Jurnal KESANS : Kesehatan dan Sains, 2023)
Background: COVID-19 booster Vaccination is a COVID-19 vaccination after a person has received a full dose of primary vaccination which aims to maintain the level of immunity and extend the period of protection. The COVID-19 booster vaccination is organized by the Government. Objective: Knowing the determinants of community willingness to vaccinate the COVID-19 booster at Pengasinan Health Center in Bekasi City. Method: This type of research was a quantitative study with a cross-sectional study design. Result and Discussion: The results showed that there was a relationship between education (p-value = 0.000), knowledge (p-value = 0.001), attitude (p-value = 0.000), the role of health workers (p-value = 0.000) and the public's willingness to vaccinate booster COVID-19 and there is no relationship between gender (p-value = 0.174) and the community's willingness to vaccinate the COVID-19 booster at the Pengasinan Health Center in Bekasi City. Conclusions: Education, knowledge, attitudes and the role of health workers are related to the community's willingness to vaccinate the COVID-19 booster at Pengasinan  Public Health Center in Bekasi City